2023
DOI: 10.1097/fpc.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Real-world pharmacogenetics of statin intolerance: effects of SLCO1B1, ABCG2, and CYP2C9 variants

Abstract: Objective The association of SLCO1B1 c.521T>C with simvastatin-induced muscle toxicity is well characterized. However, different statins are subject to metabolism and transport also by other proteins exhibiting clinically meaningful genetic variation. Our aim was to investigate associations of SLCO1B1 c.521T>C with intolerance to atorvastatin, fluvastatin, pravastatin, rosuvastatin, or simvastatin, those of ABCG2 c.421C>A with intolerance to atorvastatin, fluvastatin, or rosuvastatin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Fluvastatin and rosuvastatin also inhibited the hypercapnia-induced increase in cholesterol in lipid rafts in VERO ( Figure 4H ) and in BEAS-2B ( Supplementary Figure 6A ) cells. Of note, uptake of statins into cells is mediated by organic anion transporting polypeptide (OATP)1B1 (encoded by SLCO1B1 ), while efflux of statins from cells is mediated by the breast cancer resistance protein (BCRP, encoded by ABCG2 ) ( 44 ). In previously published work, we confirmed that SLCO1B1 and ABCG2 are transcribed in HBE cells ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fluvastatin and rosuvastatin also inhibited the hypercapnia-induced increase in cholesterol in lipid rafts in VERO ( Figure 4H ) and in BEAS-2B ( Supplementary Figure 6A ) cells. Of note, uptake of statins into cells is mediated by organic anion transporting polypeptide (OATP)1B1 (encoded by SLCO1B1 ), while efflux of statins from cells is mediated by the breast cancer resistance protein (BCRP, encoded by ABCG2 ) ( 44 ). In previously published work, we confirmed that SLCO1B1 and ABCG2 are transcribed in HBE cells ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…1,[3][4][5][6][7][8] This increases the risk of statin-associated musculoskeletal symptoms. [8][9][10] Furthermore, increased function SLCO1B1 alleles have been associated with decreased plasma concentrations of OATP1B1 substrate drugs, such as rosuvastatin, simvastatin acid, and methotrexate. 6,7,11 Moreover, inhibition of OATP1B1 can impair the hepatic uptake of OATP1B1 substrates and increase their plasma concentrations.…”
Section: Introductionmentioning
confidence: 99%